Evaluation of Road Traffic Safety Level in the State Main Road Network of Latvia - Ziedonis Lazda; Juris Smirnovs (The Baltic Journal of Road and Bridge Engineering, 2009)
Evaluation of road traffic safety level may be done using several methods. The methods of accident rate and accident frequency used in this paper provide an opportunity to analyze dangerous road sections on all state main roads of Latvia. Latvia has 15 state main roads, they lead through 24 out of 26 districts, and their total length in Latvia is 1740.8 km. Analysis of road traffic accident statistics was carried out basing on the data available at Road Traffic Safety Directorate for the time period of three years (2005–2007). Critical value of accident rate has been calculated for state main roads network and its numerical value is 1.81 accidents per 106 vehicle km. Besides, relation between traffic intensity and accident rate for state main road network of Latvia has been achieved as well.